Optimal dynamic reconfiguration of large-scale PV plant under partial shading conditions based on two reconfigurable stages - Ajmal A.M.; Ramachandaramurthy V.K.; Tomar A.; Ekanayake J.B. (John Wiley and Sons Ltd, 2023)
Dynamic models; Energy conservation; Photovoltaic cells; Comparative studies; Comprehensive analysis; Income generation; Mismatch problems; Number of switches; Optimal dynamics; Performance analysis; Photovoltaic panels; Genetic algorithms